About relationship of uneven of the Earth rotational movement and Antarctic tectonic plate - K. R. Tretyak; F. K. F. Al-Alusi (Ukrainian Antarctic Journal, 2015)
The modified algorithm for determining the parameters of Euler pole and angular velocity of tectonic plate rotation is developed with regard to continuity and uneven of time series of permanent GNSS stations daily solutions. Using the data from 27 permanent GNSS stations on Antarctic area for the period 1996-2014 years we defined position of middle Euler pole and angular velocity of plate rotation, and their annual changes. The interrelation of angular velocities change of the Earth rotation and Antarctic tectonic plate ω is established